Impact of Roughness and Friction Properties of Road Surface of Urban Streets on the Traffic Safety - Beketov, Amir; Khalimova, Shakhnoza (Communications - Scientific Letters of the University of Zilina, 2023)
Results of the study of the roughness and friction properties of the road surface of urban streets influence on the traffic safety are presented in this article. As a result of this study, an empirical dependence was obtained, reflecting the relationship between the traffic speed and a load factor under different traffic conditions; the relationship between the flow density and street capacity was also determined. The maximum permissible value of the friction coefficient for experimental streets is 0.4, and 50 % of the object of study meets the requirements of operation; 50 % does not. From the proposed graph of the relative dependence of pavement roughness and safety factor, it follows that the most dangerous are the streets, the pavement roughness of which is in unsatisfactory condition. To effectively solve the problem of destruction of the road surfaces, it is first of all necessary to eliminate the cause of the damage that occurs, not just its consequences.
Keywords: pavement roughness; road surface conditions; traffic flow; traffic safety; traffic speed; urban streets